Efektivitas Pemberian Makanan Pendamping ASI Dalam Peningkatan Status Gizi Anak Usia 6-59 Bulan - Suci Zakia Dewi; Marlenywati Marlenywati; Indah Budiastutik; Elly Trisnawati; Eka Puspitasari (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Complementary feeding (MP-ASI) is provided from 6-24 months to meet children's nutritional needs no longer fulfilled by breast milk alone. In Indonesia, suboptimal MP-ASI practices contribute to nutritional problems and growth disorders in children.Purpose: To analyze the effect of MP-ASI provision on improving children's nutritional status.Methods: Quasi-experimental one-group pretest-posttest design on 30 children aged 6-59 months in the Tayan Health Center working area, Sanggau Regency. Measurements conducted in April and August 2025. Nutritional status assessed using BB/U, TB/U, BB/TB, IMT/U, and LK/U indicators. Data analyzed with Wilcoxon Signed-Ranks Test (p<0.05).Results: Significant pre-post intervention differences (p=0.000). Most children (86.7%) improved nutritional status: BB/U good nutrition rose from 83.3% to 90%, BB/TB normal 63.3% to 73.3%, TB/U normal 63.3% to 73.3%, IMT/U good nutrition stable at 90% with 3.3% overweight risk, LK/U normal 70% to 80%. Conclusion: MP-ASI with nutrition education and active feeding effectively improves children's nutritional status and supports growth disorder prevention.